Pengaruh Loneliness, Self-Control, Dan Self Esteem Terhadap Perilaku Cyberbullying Pada Mahasiswa - Anwarsyah, Fadhli; Gazi, Gazi (‎‎‎TAZKIYA: Journal of Psychology, 2017)
This research aims to determine the effect of loneliness, self-control, self-esteem against cyberbullying to UIN Syarif Hidayatullah Jakarta student. Researchers used quantitative approach with multiple regression analysis techniques. Population and sample of this research was a UIN Syarif Hidayatullah Jakarta student. The sampling used non-probability technique that involved 261 students. The measuring instrument was adapted from a scale of cyberbullying as a theory Williard, UCLA Loneliness Scale (UCLA-LS), a measuring instrument was adapted from the scale of self-control as a theory Averill, The Rosenberg Self-esteem Scale. The results of this research showed that loneliness of self-control and self-esteem significantly affect cyberbullying with contribution 23%. There are four variables that significantly affect the cyberbullying that trait loneliness, depression, loneliness, cognitive control, and decisional control. While social desirability variable loneliness, behavioral control and self-esteem were not significant. DOI: 10.15408/tazkiya.v22i2.8401